Travmatik abdominal duvar herniasyonu: Olgu sunumu - Altuntaş, Yunus Emre; Kement, Metin; Eser, Mehmet; Gezen, Fazlı Cem; Haksal, Mustafa Celalettin; Aksakal, Nihat; Öncel, Mustafa (My University, 2013)
Travma sonrası abdominal duvarın herniasyonu nadir görülen bir durumdur. Bu tip hernilerin tanımı ve tanısı zordur. Tanı ve tedavide gecikmenin morbidite ve mortalite oranlarını artıracağı aşikardır. Bu yazıda traktör devrilmesi sonrası çoklu travma tanısıyla acil servise yatırılan 53 yaşında erkek olgu sunuldu. Hasta ameliyata alındı, posterior üretra laserasyonu sorunsuz bir şekilde tamir edildi. Fakat ameliyat sonrası dördüncü günde sistemik enflamatuvar cevap sendromu bulguları gelişti. Yapılan bilgisayarlı batın tomografisinde (BBT) sigmoid kolon segmentinin batın duvarına fıtıklaştığı görüldü. Laparotomide sigmoid kolonun fıtık sahasına perfore olduğu ve alanı kontamine ettiği görüldü. Etkilenen sigmoid kolon segmenti rezeke edilerek Hartman tipi uç kolostomi uygulandı. Çevre nekrotik dokular debride edildi. Travmatik karın duvarı hernileri özellikle geç kalınması durumlarında içi boş organların inkarserasyon ve perforasyonuna yol açarak ciddi morbidite ve mortaliteye sebep olabilirler. Bu nedenle travmatik herni olasılığı ciddi künt batın travmalı olgularda mutlaka akılda tutulmalı ve şüpheli olgularda yüksek tanı değerine sahip BBT uygulanmalıdır.

Abdominal wall hernia due to trauma is a rare condition. Diagnosis of this type of hernia still remains a major obstacle. Any delay in diagnosis and treatment will increase morbidity and mortality rates. We presented a case of a 53-year-old male patient admitted to our emergency department for multiple body traumas caused by a tumbling tractor. Patient received an urgent operation and urethral laceration was repaired. On the fourth postoperative day, systemic inflammatory response symptoms occurred. Computer tomography (CT) scan examinations revealed herniation of a sigmoid colon segment through the abdominal wall. We proceed with an exploratory laparotomy. A perforated sigmoid colon segment was detected at the herniation site. This segment was resected and a Hartman style end colostomy was done. Surrounding tissues and debris were dissected very carefully. Traumatic abdominal wall hernias can have high morbidity and mortality rates due to incarceration and perforation of tubular hollow organs, especially if there is any delay. The possibility of traumatic hernia should always be considered in cases with serious blunt trauma. CT scan examinations should be performed routinely due to their high diagnostic value in suspected conditions.
Traumatic abdominal wall herniation: Case report
Keywords: Abdominal Bilgisayarlı Tomogrofi; Abdominal Duvar Hernisi; Travma; Abdominal Computed Tomography; Abdominal Wall Hernia; Trauma